Legal Liability of Patients for Concealing Infectious Diseases as a Form of Legal Protection for Dentists - Ridlo, Himmaturojuli Rosyid; Sukmariningsih, Retno Mawarini; Hartini, M.C. Inge (Journal Evidence Of Law, 2025)
The concealment of information regarding infectious diseases by patients in dental care settings poses serious risks to dentists regarding health and legal implications. A patient's lack of transparency may hinder the provision of appropriate medical measures and potentially lead to legal disputes. This study examines the legal liability of patients who conceal information about infectious diseases to ensure legal protection for dentists. The research adopts a normative juridical approach through a literature study of statutory regulations, legal literature, and relevant court decisions. The analysis is conducted qualitatively using systematic and grammatical interpretation methods. The findings indicate that Law Number 17 of 2023 on Health establishes a legal basis for patients’ obligation to provide honest and accurate health information. Concealing an infectious disease may be classified as an unlawful act that causes both material and immaterial harm to dentists. In practice, dentists are entitled to legal protection if they suffer losses as a result of a patient's dishonesty. The discussion reveals that strengthening patients’ rights and obligations through precise legal instruments and public education on the importance of health information disclosure are essential measures to prevent disputes and safeguard dentists in performing their professional duties. Legal protection for dentists should be passive through patient liability and supported by consistent and enforceable policy and professional ethics.